Trends in Pertussis Diagnostic Testing in the United States, 1990 to 2012. Issue 1 (January 2016) - Faulkner, Amanda E.; Skoff, Tami H.; Tondella, M. Lucia; Cohn, Amanda; Clark, Thomas A.; Martin, Stacey W.
Abstract : Background: Reports of pertussis have been increasing in the US since the 1990s, and pertussis diagnostics have evolved during that time. Here, we describe temporal changes in pertussis diagnostic practices in the US during 1990 to 2012 and discuss potential implications. Methods: Pertussis cases reported through the National Notifiable Diseases Surveillance System during 1990 to 2012 were included in this analysis. Laboratory results were stratified by test type, case classification, age group and case-patient state of residence. Results: This analysis included 291, 290 cases with 64% (n = 186, 766) reporting at least 1 pertussis laboratory result. Culture and direct fluorescent antibody were the primary results reported during the early 1990s; however, polymerase chain reaction (PCR) surpassed all other test types during the late 1990s and 2000s. By 2012, more than 91% of cases with known results were tested using PCR, either alone or in combination with another test type. Before 2005, Massachusetts reported 71% of serology results, but an increasing number of states reported serologic results during 2005 to 2012. When stratified by age group, overall testing trends persist. As of 2012, culture confirmation is used infrequently across all ages, whereas the use of serology increases with age and is most prevalent among adults aged ≥20 years. Conclusions: PCR has become the primary diagnostic method, and serologic assays now are used in a majority of states. Epidemiologic trends must be considered in the context of changing diagnostic tests, and modifications to surveillance case definitions should be considered to better reflect current testing practices. Abstract : Supplemental Digital Content is available in the text.